Traditional ceremonies Mahesa Lawung as a traditional ritual of the Surakarta Palace in the Krendowahono Area, Central Java, Indonesia - Syamsi, Rahma Nur; Safitri, Olinda Ayu; Putri, Rani Rachma Astining; Manullang, Raymond Hamonangan; Rinoa Salsabila Izdihar; Setyawan, Ahmad Dwi (Generasi Biologi Indonesia, 2024)
Traditional ceremonies are a form of culture passed down from generation to generation, reflecting a society's values, beliefs, and identity. This research aims to find out and understand the meaning of the Mahesa Lawung traditional ceremony, the types of plants and animals used, and the knowledge of local communities in the Krendowahono Karanganyar Site area, Central Java. The method used in this research is a qualitative observation method, including direct interviews with each respondent. Data was collected through interviews and direct observation at the research location. The research data collected includes regional names, common names, scientific names of plants and animals species as well as parts used for offerings at Mahesa Lawung traditional ceremony, and the philosophies of the species that used in this traditional ceremony. There are 7 plants and 4 animal species used for the Mahesa Lawung traditional ceremony. The research results show that the Mahesa Lawung traditional ceremony is still carried out today, especially at the Krendowahono Site. Of the three villages used as research locations, almost all people knew about the ceremony but only heard about it and saw it briefly. The Mahesa Lawung traditional ceremony is a cultural history that needs to be preserved and maintained over time.